Phosphorus sorption and desorption in ephemeral gully erosion - Coover, James Brigham (Kansas State University, 2014)
Phosphorus (P) is an essential nutrient in crop production, but P inputs to surface waters have resulted in impairments such as eutrophication and algae blooms. Non-point sources such as agricultural fields are a main contributor of P. Kansas, being a high agricultural dependent state, has frequent fresh water body impairments. Multiple erosion and transport processes contribute to P loss. While P loss from sheet and rill erosion has been studied extensively, P loss from ephemeral gully erosion is largely unknown. The objective of this study is to understand the effects ephemeral gullies have on the transport and transformation of P. Three fields in McPherson County with well-defined ephemeral gullies were studied. Soil samples were taken in field locations that are effected by ephemeral gullies at the 0 to 2, 2 to 5, 5 to 15, and 15 to 30 cm depths. Samples were analyzed for total P, anion exchange phosphorus (AEP) (labile P), ammonium-oxalate extractable Fe, Al, and P (Fe[subscript]ox, Al[subscript]ox, P[subscript]ox), Mehlich 3 extractable Fe, Al, Ca, and P (Fe[subscript]M3, Al[subscript]M3, Ca[subscript]M3, P[subscript]M3), equilibrium phosphorus concentration at zero net sorption (EPC[subscript]0), 1:1 soil to water pH, and texture. Soil testing showed that P quantities tend to be much higher in surface soils eroded by sheet and rill erosion and lower in subsoil soil that is eroded by ephemeral gullies. The quantity of sorptive elements such as Fe and Al, were not significantly different throughout the tested area except in areas of changing soil texture. EPC[subscript]0 testing showed it was likely that P desorbs from the surface erosion of sheet and rill and is adsorbing onto the subsoil eroded from ephemeral gullies. Sediment eroded by ephemeral gullies has a P buffering capacity greater than the sediment eroded by sheet and rill, and a small quantity of ephemeral gully subsoil will have a large effect on the dissolved P concentration of runoff. Sediment, total P loss and expected dissolved P in runoff was surveyed and modeled for two of the fields. Ephemeral gullies contributed to a majority of sediment and total P loss. The addition of ephemeral gully sediment to the erosional mix of sheet and rill sediment caused the dissolved P concentration to decrease from 0.0204 to 0.0034 mg L[superscript]-1 in one field and from 0.0136 to 0.0126 mg L[superscript]-1 in another. The results of this study show that best management practices (BMPs) such as grass waterways could cause the losses of total P to decrease as much as 2 to 12 times in fields with ephemeral gullies. However, reducing ephemeral gully erosion will likely increase dissolved P concentrations up to 600% more in runoff. Therefore, BMPs need to be combined to fully control P loss from agricultural fields.
Keywords: Phosphorus Ephemeral gullies; Agronomy (0285); Soil Sciences (0481)